How the New York Secession, the 1913 Armory Show, Became the Prototype for the Contemporary Art Fair - Jeffrey Michael Taylor (Arts, 2025)
The 1913 Armory Show has long been celebrated as the moment when America was introduced to modern art. This formalistic understanding of the event, though, would miss another equally important development which would only be observed through a historical materialist methodology that would see it as a response to a crisis of over-supply in the art market. It remains the single primary exhibition staged by the short-lived Association of American Painters and Sculptors (AAPS), a secession from the National Academy of Design. Though they would not succeed in creating a long-term alternative to their rival, their exhibition expanded upon innovations by the 1912 Sonderbund exhibition in Cologne. Through an archival examination of the Armory Show’s sourcing methods, a paradigm shift can be observed leading away from the nineteenth-century salon model by changing the system of artists submitting works to a jury, to one of marketing artworks provided by dealers. This new role for dealers would lead the way to the contemporary art fair model where galleries are the key exhibition decision-makers.